Development of Bioplastics : Cassava Starch Grafted Polystyrene and Effect of Additives in Gluten - Kaewta Kaewtatip (Prince of Songkla University, 2016)
Thesis (Ph.D., Polymer Technology)--Prince of Songkla University, 2010